Analysis of the petrous portion of the internal carotid artery: Landmarks for an endoscopic endonasal approach (2014)
Objectives/Hypothesis While there are many benefits to the endoscopic endonasal approach to the infratemporal fossa, involvement of the petrous portion of the internal carotid artery (ICA) poses a unique challenge. The endoscopic endonasal approach requires establishing the relationship of the petrous ICA to anatomical landmarks to guide the surgeon. This study evaluates the relationship of petrous ICA to specific anatomic landmarks, both radiographically and through cadaveric dissections. Study Design Cadaveric and radiographic study. Methods An endoscopic endonasal approach was used to access the petrous carotid and infratemporal fossa. Dissections exposed the petrous portion of the carotid artery and identified the foramen rotundum, ovale, and spinosum. Both anatomical and radiographic representations of these landmarks were then evaluated and compared relative to the petrous carotid. Results The endoscopic endonasal approach to the infratemporal fossa with exposure of the petrous ICA afforded complete visualization of the entire segment of this portion of the ICA with limited anatomical obstruction. The foramen rotundum, ovale, and spinosum were successfully identified and dissected with preservation of their neuro/vascular contents. Computed tomography analysis calculated a mean distance to the petrous ICA of 16.34 mm from the foramen rotundum, 4.88 mm from the ovale, and 5.11 mm from the spinosum in males. For females, the values were 16.40 mm from the rotundum and 4.36 mm each from the ovale and spinosum. Conclusion An endonasal endoscopic approach to the infratemporal fossa with exposure of the petrous ICA is feasible. The anatomical landmarks can serve as both radiographic and surgical landmarks in this approach. Level of Evidence N/A. © 2014 The American Laryngological, Rhinological and Otological Society, Inc.